Coexistence of Factor VII Deficiency and Hereditary Spastic Paraplegia in Two Siblings - Hortensia De la Corte-Rodriguez; E. Carlos Rodriguez-Merchan; M. Teresa Alvarez-Roman; Ana L. Hernandez-Moreno (Case Reports in Hematology)
We present the case of two patients aged 12 years and 7 years who were referred to our hospital for factor VII deficiency inherited in an autosomal recessive pattern, who had suffered from previous multiple joint haemarthroses. They presented with fine motor symptoms and difficulty in walking. During physical examination we observed neurological symptoms (general hypotonia, muscular hypotrophy, exaggerated tendon reflexes, pes cavus, and spastic gait). Given that the symptoms were not justified by the deficiency of coagulation factor VII and on suspicion of hereditary spastic paraplegia (HSP), tests were carried out. Findings from the tests confirmed the diagnosis of HSP (axonal degeneration of the central motor pathway and pyramidal tracts), further complicated by mixed neuropathy. This disease was also inherited in an autosomal recessive pattern with no direct genetic association with factor VII deficiency. Neurological symptoms had gone unnoticed due to a history of multiple joint haemarthrosis; musculoskeletal examination led to a satisfactory differential diagnosis. Haematological prophylaxis was commenced with rFVIIa at 30 mcg/kg, three days per week. A rehabilitation programme was prescribed so that the patient could remain independent for as long as possible, based on orthosis, physiotherapy, and occupational therapy. Response to treatment is currently satisfactory and no new bleeding has presented. As far as we are aware, the coexistence of these two diseases (factor VII deficiency and HSP) has not been previously reported in the literature.